Biomedical Research Programs at Present and Future High-Energy Particle Accelerators - Patera, Vincenzo; Prezado, Yolanda; Azaiez, Faical; Battistoni, Giuseppe; Bettoni, Diego; Brandenburg, Sytze; Bugay, Aleksandr; Cuttone, Giacomo; Dauvergne, Denis; de France, Gilles; Graeff, Christian; Haberer, Thomas; et al. (Frontiers in Physics, 2020)
Biomedical applications at high-energy particle accelerators have always been an important section of the applied nuclear physics research. Several new facilities are now under constructions or undergoing major upgrades. While the main goal of these facilities is often basic research in nuclear physics, they acknowledge the importance of including biomedical research programs and of interacting with other medical accelerator facilities providing patient treatments. To harmonize the programs, avoid duplications, and foster collaboration and synergism, the International Biophysics Collaboration is providing a platform to several accelerator centers with interest in biomedical research. In this paper, we summarize the programs of various facilities in the running, upgrade, or construction phase.